Seminoma arising in the background of persistent Reteroperitoneal Woolfian duct remnants - Wazir, Rehan; Haque, Anwar Ul (International Journal of Pathology, 2018)
A 23-year-old male presented with history of mass lower abdomen. He had occasional pain and abdominaldiscomfort. Fine Needle Aspiration Cytology findings revealed atypical cells consistent withgerm cell tumor.Excisional biopsy specimen showed mass containing spermatocytic seminoma, seminalvesicle, spermatic cord and prostatic elements